Performance Evaluation of O3B Satellite Communication - al-ghadhanfari, murtadha; Sanusi , Hilmi (Journal of Methodical Computing and Communications, 2025)
Abstract: One of the potential strategies that may be utilized instead of terrestrial networks in remote and/or challenging terrain conditions is the Over Three Billion (O3b) satellite network. It has a high throughput depending on the frequency range and the weather. A geostationary satellite (GEO) is preferred over a low-earth satellite (LEO) because the LEO requires a tracking ground system, which increases the influence of elevation angle on the LEO.  O3b is a hybrid network that combines GEO and LEO benefits. By using a high frequency band, it is sensitive to changes in the weather. Rain and cloud attenuation are the two primary atmospheric attenuation factors that affect the O3b satellite's link budget in wet conditions. The impact of rain and cloud attenuation on the O3b’s throughput, SNR, and BER has been examined and simulated in this article. Rain is the most effective atmospheric attenuator on the satellite connection, according to simulations. The rain and cloud attenuation increase with frequency. The large elevation angle effect and substantial free space losses demonstrate that the 60 GHz band is not utilized in O3b satellite communications. Using 28 GHz allows for excellent throughput at elevation angles exceeding 20o, allowing for additional flexibility in communication between the ground and satellite segments. MATLAB is used for all simulations.